Synthesis, Biological Evaluation, and Binding Mode of a New Class of Oncogenic K‐Ras4b Inhibitors. (23rd September 2022) - Jeuken, Stephan; Shkura, Oleksandr; Röger, Marc; Brickau, Victoria; Choidas, Axel; Degenhart, Carsten; Gülden, Daniel; Klebl, Bert; Koch, Uwe; Stoll, Raphael; Scherkenbeck, Jürgen
Abstract: Ras proteins are implicated in some of the most common life‐threatening cancers. Despite intense research during the past three decades, progress towards small‐molecule inhibitors of mutant Ras proteins still has been limited. Only recently has significant progress been made, in particular with ligands for binding sites located in the switch II and between the switch I and switch II region of K‐Ras4B. However, the structural diversity of inhibitors identified for those sites to date is narrow. Herein, we show that hydrazones and oxime ethers of specific bis(het)aryl ketones represent structurally variable chemotypes for new GDP/GTP‐exchange inhibitors with significant cellular activity. Abstract : Ras proteins are implicated in some of the most common life‐threatening cancers. Despite intense research over the past 30 years, progress towards small‐molecule inhibitors of mutant Ras proteins is limited. Herein we show that hydrazones and oxime ethers of specific bis(het)aryl ketones represent structurally variable chemotypes for new GDP/GTP‐exchange inhibitors with significant cellular activity.